Evaluation of the Antimicrobial Activity of Selenium nanoparticles Coated Gutta-Percha Against Enterococcus faecalis and Staphylococcus aureus: An In Vitro Study - G, Manobharathi; Raghu, Sandhya (Journal of Neonatal Surgery, 2025)
Aim: The aim of this study is to enhance the antimicrobial effectiveness of conventional Gutta percha(GP) by modifying its surface with selenium nanoparticles(SeNPs). Materials And Methods: SeNPs were synthesized using a chemical reduction method by dissolving 0.2 g of selenous acid in 100 mL distilled water, followed by mixing with 0.5 g sodium borohydride dissolved in 100 mL water. The resulting SeNPs sol was stirred and stored in a brown glass container. Sterilized GP cones (size 40, Dentsply Maillefer, Switzerland) were immersed in the SeNPs solution for 24 hours to allow uniform nanoparticle deposition. This in vitro study compared the antimicrobial efficacy of SeNPs coated GP (Group 1) and conventional GP (Group 2) against Enterococcus faecalis and Staphylococcus aureus. Using the Direct Contact Test on Mueller-Hinton agar, zones of inhibition (ZOI) were measured after 24-hour incubation at 37°C. Standard bacterial strains were cultured and standardized to 0.5 McFarland before lawn inoculation. GP cones (10 mm) were placed on the plates, and antimicrobial activity was assessed by measuring ZOI diameters in triplicate. Results: The antimicrobial efficacy of SeNPs-coated GP was assessed against S. aureus and E. faecalis by measuring ZOI on agar plates, with uncoated GP as a control. Against S. aureus, uncoated GP produced a mean ZOI of 27.22 mm, while SeNPs coated samples measured 28.40 mm (20 µL) and 29.19 mm (30 µL). For E. faecalis, the corresponding values were 23.37 mm, 24.37 mm, and 25.14 mm. These results demonstrate a clear dose-dependent increase in antimicrobial activity with higher SeNPs volumes. The SeNPs coating’s redox activity and ROS generation likely underpin this enhanced bactericidal effect. Thus, SeNPs coated GP shows significantly greater antibacterial properties compared to conventional GP, suggesting potential benefits for endodontic disinfection. Conclusion: Within the limitations of the study, surface modified GP with SeNPs exhibited excellent antimicrobial properties, effectively inhibiting key microorganisms associated with root canal failure such as E.faecalis and S.aureus